Implementasi Pendekatan CRT untuk Meningkatkan Motivasi Dan Hasil Belajar Peserta Didik Kelas VIII SMPN 13 Madiun - Mardiyanti, Nur Eka Agusti; Kurdaningsih, Kurdaningsih; Sanjaya, I Gusti Made (PendIPA Journal of Science Education, 2024)
This research aimed to increase student motivation and learning outcomes. This type of research is Classroom Action Research over 2 learning cycles, which lasts for two meetings, where in one cycle there is one meeting which includes planning, implementation, observation and reflection activities. The research subjects were 31 students from class VIII B at SMPN 13 Madiun. Data collection was carried out using questionnaires, observations and evaluations. The data from this research were processed and analyzed, which showed that the highest student motivation was in the process indicators that were interesting, the learning activity process ran interestingly, and increased students' learning motivation. The learning outcomes of students in cycle 1 obtained an average score of 88.57 and a completeness level of 75%, cycle 2 obtained an average score of 96.07 with a completeness level of 89.29%. The results obtained from cycles 1 and 2 using the CRT approach can be used as input for teachers to increase students' motivation and learning outcomes in learning activities.